(3TQM GdHNGQis - (3CMeO Hf Ydj Hf eMeO Hf MLQ GdTGaYj GdcfGfj GdYSbdGfj, TgGH GdOjf CHh GdaVd, GHf MLQ, J (B852 (3g` s; (3CHh YHO Gddg eMeO Hf ESeGYjd Hf EHQGgje GdLYaj GdHNGQj, GdEeGe GdHNGQj,J (B256 (3g` s
(3ChdgG (B:s
(3eHJhQ , hChd GdehLhO efg ef HGH (B" (3hEPG CeQCI NGaJ ef HYdgG fThRkG Ch EYQGVkG (B" (3bhdg (B: (3PcQ ajg MOjK YGFTI GdSGda ai JaSjQ gPg GdBjI , hbGe GdELeGY Ydi LhGR gPG GdUdM s
(3BNQgG (B:s
(3BNQg eHJhQ , hBNQ GdehLhO efg HebOGQ hQbI ef HGH GdMPa hGdHfObI (B" (3bhdg hhbhY hGMO ef KdGKI CbQH ef hbhY hGMO ef EKfjf aGFOI (B: (3bGd YjGV s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B34 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B52s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdMOjK h GdeUWdMs